1978
DOI: 10.1172/jci109231
|View full text |Cite
|
Sign up to set email alerts
|

The Micellar Sink

Abstract: Although the importance of mixed micelles in the solubilization and biliary excretion of lipids is established, little is known about a possible role of mixed micelles in the excretion of other biliary solutes. Ultrafiltration and ultracentrifugation techniques were used to investigate the interaction between substances that are excreted in bile and biliary mixed micelles. Substances (urea, erythritol, sucrose) excreted in bile at concentrations equal to, or less than, that in plasma did not show an associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 35 publications
3
7
1
Order By: Relevance
“…They reported that Proteobacteria formed the most abundant phylum with a predominance of the Pseudomonas and Janthinobacterium genera. A similar C57BL/6 skin microbiome was described by Scharschmidt et al (22). Tavakkol et al (23) analysed the dorsal trunk skin of C57BL/6 mice and reported that this part of the skin, unlike the above-mentioned ear skin, was mainly inhabited by staphylococci, which are part of the phylum Firmicutes.…”
Section: Introductionsupporting
confidence: 59%
“…They reported that Proteobacteria formed the most abundant phylum with a predominance of the Pseudomonas and Janthinobacterium genera. A similar C57BL/6 skin microbiome was described by Scharschmidt et al (22). Tavakkol et al (23) analysed the dorsal trunk skin of C57BL/6 mice and reported that this part of the skin, unlike the above-mentioned ear skin, was mainly inhabited by staphylococci, which are part of the phylum Firmicutes.…”
Section: Introductionsupporting
confidence: 59%
“…Therefore, at higher bile salt concentrations that induce CF leakage from large unilamellar vesicles, we limit our conclusions to the observation that vesicles that still contain CF do not display any change in water permeability. Indeed, it is likely that alterations in membrane structure at concentrations near membrane solubilization are responsible for the transient increases in permeability to larger molecules observed by some groups (Scharschmidt & Schmid, 1978; and TUDC (open bars) on P f of rat liver microsomal membranes at 37°C. Neither bile salt significantly alters P f of rat liver microsomal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies of bilirubin and other organic anion secretory rates in bile showed a strong correlation with bile acid secretory rates under stimulated conditions but not during fasting (3)(4)(5)(6)(7)(8). This observation led to studies that have concluded that a strong relationship exists between biliary mixed-lipid micelles and bilirubin in addition to a variety of other organic anions, although the precise nature of the putative micellar-organic anion interaction has remained unclear (9)(10)(11)(12)(13)(14)(15). Thus, a more recent study examining this relationship failed to support the concept of a physicochemical association between biliary lipids and conjugated bilirubin (15).…”
Section: Introductionmentioning
confidence: 99%